“GOD’S NOT DEAD 2” DILEMMA: SELECTED RELIGIOUS LIBERTY ISSUES OF K-12 SCHOOL TEACHERS - Zamkowska, Iwona (Journal of Education Culture and Society, 2018)
The aim of the research is to confirm whether “God’s Not Dead” (2016) production is an adequate portrayal of religious liberty of school officials in present-day K-12 schools in the United States. The author limited the discussion to the essential problem questions inspired by the production, such as teachers’ right to express their religious views both in the formal setting of a class discussion, and out-of-class informal exchange with students and fellow faculty members. The problem was discussed against the backdrop of selected legal and legislative acts that determine the scope of teachers’ religious expression, such as selected courts’ decisions, official federal guidelines issued by the Department of Education as well as the guides published by non-government organizations. The results of the Bible Literacy Project as well as interviews with several school officials were utilized to further verify the basic concepts of the research. The source texts were analyzed using a close reading method. The study seems to prove that due to the complexity of the legal system as well as the discrepancy between the lines of decisions reached in lower courts it difficult to unambiguously assess the probability of the scenario featured in the movie. However, observable trends in case law and governmental control over teachers’ in-class speech appear to imply that the script is definitely accurate in its portrayal of a legal liability of teachers, and possibly less so in respect of the favorable outcome of the dispute.